Translation Jousts and Translation Genres: Translating Culture and Style at the Quais du Polar - Snyder, Maria (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2020)
The Quais du polar book festival in Lyon is more than a site of commerce. Instead, the category of the polar, which brings together the mystery and roman noir, reveals the potential to destabilize literary hierarchies, foreground translation, and transform the role of place in a globalized genre. Using the insights of Lawrence Venuti, Benoît Tadié and Luc Boltanski, this essay examines how, within the polar category and in the context of the festival, foreignizing translations may upend linguistic and cultural hierarchies and transform genre categories. The communal and local experience of festivals events, its rewriting of southern American authors, and its reframing of the role of readers and translators all reveal the transformative potential of the polar and its cultural reception.